Highly Efficient Catalytic Hydrogen Evolution from Ammonia Borane Using the Synergistic Effect of Crystallinity and Size of Noble-Metal-Free Nanoparticles Supported by Porous Metal–Organic Frameworks - Liu, Penglong; Gu, Xiaojun; Kang, Kai; Zhang, Hao; Cheng, Jia; Su, Haiquan (ACS applied materials & interfaces, 2017)
A series of nonprecious metal nanoparticles (NPs) supported by metal–organic framework MIL-101 were synthesized using four methods and their catalytic performance on hydrogen evolution from ammonia borane (NH3BH3) was studied. The results showed that the crystalline Co NPs with size of 4.5–8.5 and 14.5–24.5 nm had low activities featuring the total turnover frequency (TOF) values of 9.9 and 4.5 molH2 molcat –1 min–1, respectively. In contrast, the amorphous Co NPs with size of 1.6–2.6 and 13.5–24.5 nm exhibited high activities featuring the total TOF values of 51.4 and 22.3 molH2 molcat –1 min–1, respectively. The remarkably different activities could be ascribed to the different crystallinity and size of Co NPs in the catalysts. Moreover, the ultrasound-assisted in situ method was also successfully applied to bimetallic systems, and MIL-101-supported amorphous CuCo, FeCo and NiCo NPs had the catalytic activities with total TOF values of 51.7, 50.8, and 44.3 molH2 molcat –1 min–1, respectively, which were the highest in the values of the reported non-noble metal Co-based catalysts. The present approach, namely, using the synergistic effect of crystallinity and size of metal NPs, may offer a new prospect for high-performance and low-cost nanocatalysts.